2015
DOI: 10.1016/j.ijproman.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Bridging BIM and building: From a literature review to an integrated conceptual framework

Abstract: A Building Information Model (BIM) is at risk of being 'blind and deaf' if its contained information cannot be synchronized with ongoing building processes in a real-time manner. Previous studies have attempted to explore solutions to the problem, with a view to making BIM a more useful decision-support system. However, an integrated conceptual framework summarizing these studies and structuring future development in the area is missing. Based on an ex post facto critical review of 75 papers of this kind publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(131 citation statements)
references
References 83 publications
0
125
0
6
Order By: Relevance
“…Prefabricated buildings need to ensure the close coordination between prefabricated production links and field construction links so that the prefabricated component production links can achieve fine and quantitative management [2]. Some foreign scholars focus on the application of BIM technology to improve the intelligent level of prefabricated component production process and achieve fine management so as to improve the efficiency of prefabricated components production [6,7]. Mohammed and Liu made use of the visualization advantage of BIM technology, integrated the schedule plan, and guided by the task of the factory, proposed the BIM-4D simulation framework to carry out fine management on the production process, quality, and quantity of prefabricated components in the factory but lacked in the development of BIM technology platform [16].…”
Section: Research On the Management Of Prefabricated Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prefabricated buildings need to ensure the close coordination between prefabricated production links and field construction links so that the prefabricated component production links can achieve fine and quantitative management [2]. Some foreign scholars focus on the application of BIM technology to improve the intelligent level of prefabricated component production process and achieve fine management so as to improve the efficiency of prefabricated components production [6,7]. Mohammed and Liu made use of the visualization advantage of BIM technology, integrated the schedule plan, and guided by the task of the factory, proposed the BIM-4D simulation framework to carry out fine management on the production process, quality, and quantity of prefabricated components in the factory but lacked in the development of BIM technology platform [16].…”
Section: Research On the Management Of Prefabricated Componentsmentioning
confidence: 99%
“…BIM is mainly used to process and analyze the data information of various components in the model through the combination of related software and technical equipment so as to provide a platform for project participants to share information and resources and optimize the process management of the project [6][7][8]. RFID is a noncontact automatic identification technology used for information collection, which is usually composed of an RFID reader and RFID tag.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the study of synchronization data between BIM and on-site real-time building process is a hotspot over years, many methods and technologies, such as laser scanning, radio frequency identification (RFID), augmented reality (AR), geographic information system (GIS), etc., have been applied to acquire and management these sophisticated data for 'bridging BIM and building (BBB)' . (Chen et al 2015).…”
Section: ) Technological Factorsmentioning
confidence: 99%
“…In the technology fields, enterprises paid more attention to building quality, operation performance of construction machinery, and maturity of industrialization technology. Furthermore, some research projects focused on information and communication technology in the construction industrialization fields [37,40,64,65]. Experts suggested that the application level of prefabricated components in projects depended on the implementation of construction industrialization technology [37,40,64,65].…”
Section: Challenges In Industrializationmentioning
confidence: 99%